PRODUKSI BAHASA SEORANG ’NATIVE BILINGUAL’ ANAK USIA 5 TAHUN - Tandiana, Soni T (Parameter, 2014)
Abstract: An analysis on psycholinguistics field has been conducted by the writer to find out the speech produced by the 5 years old ’native bilingual’ child namely Helga Claresta Raudina. Descriptive qualitative is used as the method of the research, the data required are obtained by interviewing the respondent. The lexical and grammatical types of speech produced by the respondent are analysed based on the psycholinguistics theories. This research is done to give valuable information and description of how the five years old child produces their languages. Abstrak: Analisis psikolinguistik telah dilakukan oleh penulis untuk mengetahui kemampuan berbicara bilingual anak 5 tahun, yaitu Helga Claresta Raudina. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Data diperoleh dengan mewawancarai responden. Jenis leksikal dan gramatikal berbicara dihasilkan oleh responden dianalisis berdasarkan teori psikolinguistik. Penelitian ini dilakukan untuk memberikan informasi yang berharga dan deskripsi tentang bagaimana seorang anak berusia lima tahun memproduksi bahasa.